5-Hydroxymethylcytosine Is Not Present in Appreciable Quantities in Arabidopsis DNA. Issue 1 (1st January 2015) - Erdmann, Robert M; Souza, Amanda L; Clish, Clary B; Gehring, Mary
Abstract: 5-Hydroxymethylcytosine (5-hmC) is an intermediate in active demethylation in metazoans, as well as a potentially stable epigenetic mark. Previous reports investigating 5-hydroxymethylcytosine in plants have reached conflicting conclusions. We systematically investigated whether 5-hmC is present in plant DNA using a range of methods. Using the model organism Arabidopsis thaliana, in addition to other plant species, we assayed the amount or distribution of 5-hydroxymethylcytosine by thin-layer chromatography, immunoprecipitation-chip, ELISA, enzymatic radiolabeling, and mass spectrometry. The failure to observe 5-hydroxymethylcytosine by thin-layer chromatography established an upper bound for the possible fraction of the nucleotide in plant DNA. Antibody-based methods suggested that there were low levels of 5-hmC in plant DNA, but these experiments were potentially confounded by cross-reactivity with the abundant base 5-methylcytosine. Enzymatic radiolabeling and mass spectrometry, the most sensitive methods for detection that we used, failed to detect 5-hydroxymethylcytosine in A. thaliana genomic DNA isolated from a number of different tissue types and genetic backgrounds. Taken together, our results led us to conclude that 5-hmC is not present in biologically relevant quantities within plant genomic DNA.